Guidelines for developing an edutainment courseware for visually impaired people - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin (2006)
Visually impaired people have lack access to information disseminated through computers and computer applications including courseware. Most coursewares are developed without addressing visually impaired people as a part of the users. This project proposes and validates the guidelines of an edutainment courseware for visually impaired people in four perspectives: general interaction, text, audio, and graphic and animation.An English edutainment courseware was developed and further tested to validate the proposed guidelines. 30 guidelines were listed, of which five are for the general interaction, eight for the text, eight for the audio, and nine for the graphic and animation.Comments from the participants indicate that the courseware performed accordingly to their expectation and provided guidelines might help the designers to come out with coursewares in the future.